(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this study, the Lindelöf property of spaces will be examined across three topologies, referred to as tri-Lindelöf spaces. Furthermore, the characteristics of these spaces will be analyzed in relation to Lindelöf spaces. Several theoretical results have been presented and proven, and various well-known theorems concerning Lindelöf spaces have been extended to accommodate three topologies. An illustrative examples are provided to support the findings.